A Possible Advanced Hypsithermal Position of the Donjek Glacier - Johnson, P.G. (ARCTIC, 1972)
The history of the [Donjek] glacier from 1935 to the present is well documented photographically . Documentation of the Hypsithermal and Wisconsin history of the glacier is less abundant. . During the summer of 1970 the terminus area of the Donjek Glacier and the lower part of the glacier valley were investigated for evidence of its Hypsithermal position. No evidence was found in the valley occupied by the glacier to indicate that it had retreated back into the valley from the Donjek River Valley. The inclusion of 'Slims Soil' . in the material of the Neoglacial moraine complex of the glacier indicates that there must have been some retreat up valley of the moraine position before the Neoglacial re-advance. Down valley from the Neoglacial moraines there is evidence for a relatively recent, probably Hypsithermal, ice marginal position. This evidence is in the form of a lateral moraine, terminal moraine remnants and the distribution and development of the Hypsithermal Slims Soil and volcanic ash. Unfortunately no material was found which could be dated by radiocarbon techniques to verify the age of the features. The glacial landforms are relatively easily identified when compared with the highly denuded forms which represent the pre-Neoglacial periods found elsewhere in the Donjek Valley. . It is considered that there is evidence for a stable phase of the Donjek and Kluane Glaciers late in the Hypsithermal period. This position is down valley of the Neoglacial maximum position which contrasts with the documented situation in the Kaskawulsh Valley. Late in the Hypsithermal the glaciers retreated from this stable position, the Kluane Glacier retreating to a Neoglacial position 15 miles up valley and the Donjek Glacier apparently retreating only a short distance before readvancing to its Neoglacial maximum position.